PENGARUH LIKUIDITAS, STRUKTUR ASET DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PADA PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Africa, Laely Aghe; Vonny Comelia (Universitas Maarif Hasyim Latif, 2025)
The purpose of this research is to examine the influence of liquidity, assets structure, and firm size to the capital structure of conventional banking companies which are listed in the Indonesia Stock Exchange from 2017 to 2020. This study uses quantitative method and linier regression analysis with SPSS Version 20. Firm size variable has significant influence to the capital structure, while liquidity and asset structure variables have no significant influence to the capital structure. This study is expected to serve as a guideline for banking management in making policies on company performance, as measured by Liquidity, Credit, and olvency risks so that banking companies have their own guidelines in determining policies related to banking operations to be able to bring benefits to the management and banking stakeholders.